Refusing Without “No”: The Way Lecturers Indicate Disagreement of Asian Efl Learners In Speaking Class - Novalina, Niyan Wahyu; Setiawan, Slamet; Mustofa, Ali (International Journal for Educational and Vocational Studies, 2019)
Refusal is a part of face threatening act which belong to one of politeness. Refusal is being phenomenon in language education especially in classroom. Learners often refuse lecturers’ instruction when they teach in the class. One of refusal strategies is disagreement which is a part of traditional politeness theories. In language teaching, not only learners but also lecturers also often disagree with the learners and the disagreement is also necessary for the learners. In this study, lecturers used linguistic markers to express disagreement in mitigating the face threatening. In Asian context, there were vary disagreements which were expressed by Asians. In this study, head movement and hand gesture is analyzed as disagreement of linguistic markers to stress the utterances in implicit meaning. They might become the way of disagreement communication for lecturers who taught language education in EFL context. This study observed lecturers’ disagreements in Asian language classroom context with heterogeneous learners (Indonesian, Malaysian, and Thai EFL learners). The result of this study is lecturers disagree for dispreferred options in certain aspect and the silence was minimized to avoid negative gesture or head movement. The way of lecturer in disagreement influenced by western culture when respond the learners’ refusal act.